Analyzing the Contents of a Large, Public Online Peer Support Forum for Obsessive-Compulsive Disorder: Thematic Analysis - Nora Yanyi Sun; Christopher Pittenger; Terence Ching (JMIR Formative Research)
Abstract BackgroundObsessive-compulsive disorder (OCD) is a debilitating chronic anxiety disorder with low rates of remission. r/OCD is a peer support forum hosted by the Reddit website with over 180,000 users and 100‐200 new posts daily. While peer support has been associated with improved treatment adherence and outcomes, forums can also be an outlet for performing and accommodating compulsions (eg, seeking and receiving reassurance), which can ultimately exacerbate OCD. ObjectiveThis study aims to inductively assess what types of content are posted on r/OCD, an online peer support forum for individuals with OCD, to better understand the prevalent topics, dynamics, and norms of such online communities. MethodsTo describe the explicit content of the forum, 132 new posts with a total of 739 comments added to the subreddit within a 24-hour period from August 4, 2023, to August 5, 2023, were manually downloaded and coded using inductive thematic analysis. Though posts beyond the first 24 hours were downloaded, saturation of ideas was observed after the first 110 posts, and thus, no posts after the first 24 hours were included in the analysis. Through inductive thematic analysis, codes were organized into overarching themes. ResultsFour main themes emerged during analysis: (1) validating OCD symptoms (n=69 total posts and comments), (2) connecting with peers with similar OCD themes (n=512), (3) coping with symptoms (n=280), and (4) sharing treatment experiences and advice (n=118). Many posts involved users describing their symptoms, questioning if a particular symptom was OCD, and asking other users if they had similar experiences. Users frequently categorized their OCD into subtypes using abbreviations (eg, “ROCD” [relationship OCD]) to seek others with similar experiences. A minority of posts solicited and provided advice on therapy and medication. Users were supportive and encouraging of each other’s recovery journeys. ConclusionsOnline peer support forum users demonstrated substantial knowledge of OCD and treatments; these forums enable users to receive social support and exchange helpful information and peer experiences related to seeking medical treatment. However, many users use the platform to connect with others experiencing similar subtypes of OCD or to seek confirmation that their symptoms are OCD, which is promoted by community norms and may suggest they are reassurance-seeking. Close moderation by health care professionals and restricting detailed sharing of OCD symptoms to prevent reassurance-seeking may be important for ensuring a net positive impact of online peer support forums for OCD. In addition, clinicians should consider if their patients may be reassurance-seeking on this and similar OCD forums, given their popularity. Future studies should conduct interviews with users and investigate patterns of user ability to further understand the potential harms and benefits of online peer support forums.